Influence of pressurised liquid extraction and solid–liquid extraction methods on the phenolic content and antioxidant activities of Irish macroalgae. (3rd December 2012) - Tierney, Michelle S.; Smyth, Thomas J.; Hayes, Maria; Soler‐Vila, Anna; Croft, Anna K.; Brunton, Nigel
Summary The efficiencies of pressurised liquid extraction (PLE) and a traditional solid–liquid extraction (SLE) at extracting antioxidant polyphenols from Irish macroalgae Ascophyllum nodosum, Pelvetia canaliculata, Fucus spiralis and Ulva intestinalis were compared. PLE was more effective for extracting polyphenols with acetone/water (80:20); however, when food‐friendly solvents of ethanol/water (80:20) and water were employed, SLE resulted in higher phenolic content in brown macroalgal extracts. For example, the Fucus spiralis SLE water and ethanol/water extracts displayed total phenolic contents (TPCs) of 130.58 ± 2.78 and 142.81 ± 1.77 μg phloroglucinol equivalents (PGE) mg−1 sample, respectively, compared with TPCs of 90.79 ± 1.16 and 124 ± 6.54 μg PGE mg−1 sample for the corresponding PLE extracts. All SLE aqueous ethanolic macroalgal extracts possessed higher DPPH radical scavenging abilities (RSA) and ferric reducing antioxidant power (FRAP) than their PLE equivalents. This study indicates that the application of high extraction temperatures (50–200 °C) and pressures (500–3000 psi) used in PLE does not enhance the antioxidant activities of macroalgal extracts relative to SLE extraction. The ability to produce antioxidant food‐friendly macroalgal extracts using SLE could represent significant cost reductions on an industrial scale further enhancing the potential of macroalgal polyphenols to be used in functional food preparations.